Genetic transformation for hairy root induction and enhancement of secondary metabolites in asw agandha (withania somnifera (L) dunal) - Smini Varghese (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2006)
The present study entitled ‘Genetic transformation for hairy root induction and enhancement of secondary metabolites in Aswagandha (Withania somnifera (L.) Dunal) was carried out at the Centre for Plant Biotechnology and Molecular Biology and Biochemistry Laboratory of the College of Horticulture, Vellanikkara and the Biochemistry Laboratory of Aromatic and Medicinal Plants Research Station, Odakkali. The study was undertaken to standardize the in vitro regeneration protocol in W. somnifera from different explants, to standardize the genetic transformation using Agrobacterium rhizogenes, to standardize the biochemical techniques for the estimation of secondary metabolites in roots and also to enhance the secondary metabolite production in the hairy root cultures of W. somnifera.